Evaluating the role of vitamin D metabolites and intact parathyroid hormone across chronic kidney disease stages - Hussain Rafal Haider; Haddad Nazar S.; Alsultani Ali Jasim (Acta Marisiensis - Seria Medica)
Background: Chronic kidney disease (CKD) is defined as abnormal kidney structure or function that last over three months. Its prevalence increases with age, affecting 38% of individuals aged 65 years and older. Key biomarkers for assessing CKD severity include a low estimated glomerular filtration rate (eGFR) and increased albumin levels in urine, determined by the albumin-to-creatinine ratio (ACR). 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D are impaired in CKD patients due to reduced renal function, leading to deficiencies in active vitamin D forms and contributing to secondary hyperparathyroidism (SHPT). This study evaluated the role of vitamin D metabolites and intact parathyroid hormone levels in different stages of CKD.